Effect of Noise Application on Hearing Following Exogenous Glucocorticoid Exposure an Experimental Animal Study - Sakallioglu, Oner; Yalcin, Sinasi; Kaymaz, Figen; Erbil, Kadriye Mine Ergun; Alpay, Hayrettin Cengiz; Hayran, Hatice Murvet (Ortadogu Ad Pres & Publ Co, 2012)
Objective: The aim of this study is to investigate the effect of exogenous glucocorticoid exposure in the prenatal period on hearing, and the effectiveness of an antioxidant, 'aminoguanidine', on the prevention of the inner ear injury. Material and Methods: Twelve pregnant Sprague-Dawley rats were injected with dexamethasone or distilled water beginning from 14(th) day of gestation to delivery. Test subjects were exposed to 110 dB of noise for four hours in a sound isolated environment in order to create a stress effect, when they became two months old. Test subjects were divided into three groups. Group 1: The ones whose mothers were injected with distilled water and who were exposed to 110 dB noise. Group 2: The ones whose mothers were injected with dexamethasone and who were exposed to 110 dB noise. Group 3: The ones whose mothers were injected with dexamethasone and who were exposed to 110 dB noise, and administered 200 mg/kg/day aminoguanidine. Effects of noise and aminoguanidine on hearing and the inner ear were assessed with brainstem evoked response audiometry (BERA) and electron microscopy. Results: Improvement of hearing thresholds of test subjects in group 1 and group 2 two months after noise exposure was statistically significant when compared to the thresholds obtained 48 hours after noise exposure (p<0.05). The temporary threshold shifts were observed mostly in group 3 (injected with aminoguanidine). An improvement of 13.75 dB was evident in the hearing thresholds in group 3 test subjects two months after noise exposure while hearing thresholds 48 hours after noise exposure was 3.75 dB better than the hearing thresholds of test subjects in group 1 (10 dB) and group 2 (10 dB). This difference was not statistically significant (p>0.05) and it was indicated that the application of aminoguanidine was not beneficial. Conclusion: Exposure to the exogenous glucocorticoids in prenatal period does not make the inner ear susceptible to the effect of noise. Aminoguanidine was not found effective to prevent possible injury.
Ekzojen glukokortikoidlere maruziyet sonrası gürültü uygulanmasının işitme üzerine etkisi deneysel hayvan çalışması
Keywords: Glucocorticoids; hearing; prenatal exposure delayed effects